The Influence of Economic Growth, Job Opportunity and People Prosperity on Islamic Banking Growth In Six Provinces in Java Island - Sudana Sudana; Lina Marlina (International Journal of Nusantara Islam, 2019)
The research was aimed to know the causality relations among the variables of economics growth, job opportunity, and people prosperity on the Islamic banking growth in six provinces in Java island. There was a phenomenon that during 2009 until 2018, the Indonesia economics growth was high meanwhile the Islamic banking growth grew insignificantly. The method used in the research was panel data analysis with the approach of fixed effect method. Meanwhile, data used in the research was secondary data. From the regression test result, it showed that there was a significant influence among the economics growth, job opportunity and people prosperity on the Islamic banking growth in six provinces in Java island.